Exploring Student Algebraic Thinking to Solve TIMSS Problems in Terms of Accommodator Learning Styles - Zahiroh, Lutfiyya Fajar; Masduki, Masduki (Universitas Islam Lamongan, 2024)
This study aims to explore students' algebraic thinking skills in solving Trends International Mathematics and Science Study (TIMSS) problems in terms of accommodator learning styles. The research design used is a case study with a qualitative analysis approach. The results showed that accommodating subjects were able to meet the indicators of algebraic thinking, namely generalization, abstraction, analytical thinking, dynamic thinking, and modeling. However, the lack of accuracy in performing calculation operations causes the answers obtained by the subject to be less precise on abstraction, analytical thinking, and dynamic thinking problems. The characteristics of subjects with accommodator learning styles who are more likely to use intuition in solving problems influence students' ability to solve problems related to algebraic thinking.